Influence of Probiotics and Acidifier supplementation on Growth, Carcass Characteristics and Economics of Feeding in Broilers - Rout, S. K.; Pradhan, C. R.; Rath, Rajashree; Panda, N.; Panigrahi, B.; Pati, P. K. (Indian Journal of Animal Nutrition, 2018)
One hundred and fifty, day-old Vencobb broiler chicks of either sex with uniform body weight were randomly assigned to four treatments of three replicates each having 10 birds. The chicks in all the groups were fed with starter ration up to 21 days and finisher ration from 22 to 42 days of age as per BIS (1992) recommendations, however, in treatments T2, T3 and T4, the chicks were also provided with probiotics @ 50 g,acidifier @ 2 kg and probiotics @ 50 g + acidifier @ 2 kg/tonne of feed, respectively. The basal diet served as treatment T1. Body weight gain was higher (P